Pengaruh jumlah nozzle terhadap kinerja turbin pelton sebagai pembangkit listrik di Desa Sumber Agung Kecamatan Suoh Kabupaten Lampung Barat - Dwi Irawan; Eko Nugroho; Eko Widiyanto (Universitas Muhammadiyah Metro, 2020)
A micro hydro power plant, or commonly known as a turbine is a power plant that utilizes the potential energy of water to be converted into mechanical energy which is then converted into electrical energy using a generator. The Pelton turbine is an extension of the impulse turbine with a split some blades dividing the jet into two equal beaks which are reversed sideways at the turbine wheel. This study aims to determine the effect of the number of nozzles to output power, efficiency, and electric power produced. In this study, a Pelton type water turbine was applied to a water source flowing from the mountains with a head of 26 m and 0.003167 m3/s water discharge. This study used 3 variations of the number of nozzles (single, double, and triple nozzle) with 9 mm outer diameter of nozzle and 35 mm nozzle length. The results of the research conducted, the turbine power is 419.53 watts, the turbine efficiency is 52%, and the generator power is 360 Watts for triple nozzle variation. The turbine power obtained is 388.83 Watts, the turbine efficiency is 48%, and the generator power is 234 Watts for double nozzle variation. And the power obtained is 367.47 Watts, the turbine efficiency is 45%, and the generator power is 175 Watts for single nozzle variations.